Two-dimensional ferroelastic topological insulators in single-layer Janus transition metal dichalcogenides MSSe(M=Mo, W) - Ma, Yandong; Kou, Liangzhi; Huang, Baibiao; Dai, Ying; Heine, Thomas (Physical Review B, 2018)
Two-dimensional topological insulators and two-dimensional materials with ferroelastic characteristics are intriguing materials and many examples have been reported both experimentally and theoretically. Here, we present the combination of both features - a two-dimensional ferroelastic topological insulator that simultaneously possesses ferroelastic and quantum spin Hall characteristics. Using first-principles calculations, we demonstrate Janus single-layer MSSe(M=Mo,W) stable two-dimensional crystals that show the long-sought ferroelastic topological insulator properties. The material features low switching barriers and strong ferroelastic signals, beneficial for applications in shape memory devices. Moreover, their topological phases harbor sizable nontrivial band gaps, which support the quantum spin Hall effect. The unique coexistence of excellent ferroelastic and quantum spin Hall phases in single-layer MSSe provides extraordinary platforms for realizing multipurpose and controllable devices.
CRIS-Team Scopus Importer:2022-04-14